Pengaruh Struktur Modal, Pertumbuhan Penjualan dan Ukuran Perusahaan terhadap Kinerja Keuangan - Septria Vanora; Alya Budiantini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Industrial sector companies face increasing competitive pressure, making financial performance an essential indicator of operational efficiency and long-term sustainability. However, inconsistencies in previous empirical findings regarding the influence of capital structure, sales growth, and firm size highlight the need for further examination. This study aims to provide empirical evidence on how these three factors affect the financial performance of industrial sector companies listed on the Indonesia Stock Exchange during 2020-2024. Using a quantitative associative approach, the research analyzes 120 observations from 24 companies selected through purposive sampling. Secondary data were obtained from audited annual reports and processed using descriptive statistics and panel data regression with Eviews-12. The findings show that, partially, sales growth has a significant positive effect on financial performance, while capital structure and firm size do not show a significant influence. Meanwhile, the simultaneous test indicates that capital structure, sales growth, and firm size collectively have a significant effect on financial performance. These results suggest that improvements in financial performance within the industrial sector are more strongly driven by the ability to increase sales rather than by capital structure decisions or firm size.